The flexural behavior of cold-formed steel composite beams. (1st September 2020) - Shi, Yu; Yang, Kaidi; Guan, Yu; Yao, Xinmei; Xu, Lei; Zhang, Haibin
Highlights: The flexural performance of cold-formed steel composite beams was investigated. The full-scale flexural tests were carried out on composite beams. Different slab materials and shear transfers were taken into consideration in tests. Parametric studies were conducted through verified finite element models. A method is provided to evaluate the elastic moment capacity of the beams. Abstract: In this study, six full-scale specimens were tested to investigate the flexural behavior and capacity of cold-formed steel composite floors. Three different shear transfer mechanisms, i.e. slab-to-deck interfacial epoxy, screw, and Z-tab connector, were tested with the two different slab materials, i.e., gypsum-based self-leveling underlayment and lightweight concrete with fine aggregate. It was found that the primary failure mode of the specimens was shear buckling of the joist web. The test results indicated that the shear transfer mechanisms exhibited different degrees of effect on the flexural performance of specimens with different slab materials. A finite element model was established and validated by the test results. The results of the extensive parametric investigation indicated that the section depth, thickness, and steel strength of the cold-formed steel joists had considerable influences on the flexural behavior of the composite beams whereas the deck screw spacing varied from 252 mm to 504 mm had an insignificant effect. Finally, a method was proposed to evaluate the elastic flexural capacity of cold-formed steel composite beams.